Highly Selective Synthesis of Ortho‐Prenylated Phenols and Chromans by using a New Bimetallic CuAl‐KIT‐5 with a 3D‐Cage‐type Mesoporous Structure. Issue 4 (17th September 2012) - Varghese, Shaji; Anand, Chokkalingam; Dhawale, Dattatray; Mane, Gurudas P.; Wahab, Mohammad A.; Mano, Ajayan; Raj, George Allen Gnana; Nagarajan, Samuthira; Vinu, Ajayan
<x xml:space="preserve">Abstract</x> A nice piece of KIT: The first synthesis of a new bimetallic 3D‐cage‐type mesoporous catalyst CuAl‐KIT‐5 and its remarkable performance for the highly selective synthesis of ortho‐prenylated phenols and chromans is reported.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>